Gateway to the North? Contingent Journeys at the Mexico‐Guatemala Border. (10th November 2020) - Galemba, Rebecca B.; Dingeman, Katie; DeVries, Kaelyn
Abstract: As insecurity in Central America persists and avenues for asylum in the U.S. constrict, migrants are exploring options in Mexico—to seek humanitarian relief or to bide time as they consider whether to continue north, settle, or return. Based on interviews with migrants and shelter staff at the Mexico‐Guatemala border in the summer of 2017, this article applies contingency logics (Bledsoe 2002) to analyze how proximate social ties, accumulated experiences, and harsh ordeals inform how migrants make decisions, change their minds, and re‐envision destinations amid uncertainty. Complicating tensions between mobility/immobility and settlement/transit, we demonstrate how decisions to settle, seek protection, or wait in Mexico may be socially understood as fostering migrants' larger goals to continue their journeys and pursue their migratory aspirations. However, given Mexico's expanding deportation apparatus and the unpredictability of options in Mexico, such forms of waiting also risk consigning migrants to indeterminate waiting, vulnerability, and entrapment. Resumen: Debido a la inseguridad y a las restringidas posibilidades de asilo en Estados Unidos, los migrantes están explorando sus opciones en México: buscar ayuda humanitaria o esperar mientras deciden continuar hacia el norte, establecerse o regresar a sus lugares de origen. Este artículo se basa en entrevistas realizadas con migrantes y personal de los albergues en la frontera México‐Guatemala durante el verano de 2017 y aplica lógicas de contingencia (Bledsoe 2002) para analizar las formas en que las relaciones sociales cercanas, las experiencias acumuladas y la adversidad determinan cómo los migrantes toman decisiones, cambian de opinión y replantean sus destinos en medio de la incertidumbre. Por otro lado, las complejas tensiones existentes entre movilidad/inmovilidad y asentamiento/tránsito evidencian cómo la decisión de establecerse, buscar protección o esperar en México pueden entenderse como si promovieran el objetivo de los migrantes de continuar sus viajes y aspiraciones migratorias. Sin embargo, dado el creciente aparato de deportación y la imprevisibilidad de las opciones en México, estas formas de espera también podrían condenar a los migrantes a la vulnerabilidad, a esperas indeterminadas y al aprisionamiento.